2016
DOI: 10.1186/s13104-016-1845-5
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of physicians on chronic kidney disease and their attitudes towards referral, in two cities of Cameroon: a cross-sectional study

Abstract: BackgroundChronic kidney disease (CKD) is frequently unrecognized by non-nephrology physicians. There is an ongoing governmental program to create hemodialysis centers in the ten regions of Cameroon, where a previous study reported high levels of late referral to nephrologists. We aimed to assess the knowledge of physicians on CKD and their attitudes regarding referral.MethodsA questionnaire based on the Kidney Disease Outcome Quality Initiative Guidelines of 2002 was self-administered to general practitioners… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
16
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 18 publications
(23 reference statements)
5
16
1
Order By: Relevance
“…The majority recognized diabetes mellitus, hypertension, renal stone disease and chronic glomerulonephritis as being risk factors for CKD. This was similar to results noted in a study in Cameroon [46], as well as in a web-based survey in the US [49]. Several studies have shown an increased risk for CKD among individuals with diabetes, hypertension, autoimmune diseases, urinary tract infections, stone diseases, and older age, among others [50].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The majority recognized diabetes mellitus, hypertension, renal stone disease and chronic glomerulonephritis as being risk factors for CKD. This was similar to results noted in a study in Cameroon [46], as well as in a web-based survey in the US [49]. Several studies have shown an increased risk for CKD among individuals with diabetes, hypertension, autoimmune diseases, urinary tract infections, stone diseases, and older age, among others [50].…”
Section: Discussionsupporting
confidence: 89%
“…The potential complications of CKD were identified by a majority of the respondents, but fewer attending doctors (66.7%) identified cardiovascular disease as a complication of CKD. The most commonly identified complication was anemia, similar to other studies [38,45,46,49].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Chronic kidney disease (CKD) is a major public health issue [1], and its prevalence is dramatically increasing worldwide. Moreover, CKD patients have higher cardiovascular risk and mortality rates in comparison to the general population [2][3].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, many patients with CKD will require renal replacement therapy, which represents an economic burden for health systems [2]. Prevention, early detection and appropriate care are cost-effective strategies, especially in resource-limited countries, where access to renal therapies is often conditioned by nancial constraints.…”
Section: Introductionmentioning
confidence: 99%